Integrative Art Therapy to Improve Emotional and Behavioral Problems among Children: A Systematic Review - Priyanka Saikia; Sonia Pereira Deuri (Indian Journal of Psychiatric Nursing)
Children with emotional and behavioral difficulties can benefit from combining medical and psychosocial treatments. Integrative art therapy (IAT) uses art forms such as painting, dance, music, and drama to help children express their emotions and improve well being. People commonly apply IAT to support children and adolescents with mental health challenges. The aim of this review is to present an overview of the specific elements of art therapy interventions that have demonstrated effectiveness in reducing emotional and behavioral problems in children. This systematic review searched major databases such as Google Scholar, PubMed, PsycINFO, and Scopus for articles from January 1990 to November 2023 and conducted a detailed review based on selection criteria. The searches were further scrutinized following the Preferred Reporting Items for Systematic Reviews and Meta Analyses guidelines. We excluded studies without intervention, those involving the adult population, those involving children with major mental disorders, studies conducted in languages other than English, and those lacking outcome measures. A total of 11 studies out of 67 met the inclusion criteria, and the majority of the studies included in the review were 7 randomized controlled trials and 2 single group pre–post design studies. Studies found that the use of IAT benefits emotional and behavioral issues, depressive mood, anxiety, and distress tolerance. However, the varying methodologies and limited sample sizes in the reviewed studies call for further investigation to establish clearer efficacy and delineate optimal therapeutic practices. IAT is becoming a vital part of psychosocial interventions for addressing children’s emotional and behavioral challenges. This review highlights its potential, calling for more research to solidify its evidence and inform practice. It also emphasizes art therapy’s adaptability in meeting the unique needs of children and adolescents, leading to positive psychosocial outcomes.